Medical Tourism Di Indonesia: Analisis Hukum Tentang Peluang Dan Tantangan - Nadia Mahza Prameswari (Perspektif Administrasi Publik dan hukum, 2024)
Medical tourism is a medical activity that is included with tourism activities. Currently, medical tourism has become a promising trend for Indonesia. This is supported by the potential of its natural beauty. However, there are challenges related to medical tourism itself. Thus, the problem of this research is how to analyze the law regarding the opportunities and challenges of medical tourism in Indonesia. The aim of this research is to determine the legal analysis of medical tourism in Indonesia. This research uses a normative juridical approach, qualitative descriptive research specifications, library study data collection methods and qualitative data analysis methods. The results of this research are the enactment of Minister of Health Regulation no. 76 of 2015 concerning Medical Tourism Services, the health industry in Indonesia has a legal umbrella that can provide opportunities for Indonesia in competitions for providing medical tourism. However, the absence of clear and specific legal regulations regarding medical tourism guides, as well as the weak legal framework for protecting personal data regarding patient medical records, especially for foreign patient data, can be a challenge for medical tourism. Thus, the government needs to overcome these challenges and increase existing opportunities.